ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SWASTA NASIONAL SEBELUM DAN SESUDAH PENERAPAN ARSITEKTUR PERBANKAN INDONESIA - Sri Rahayu Puspita Sari (Universitas Gunadarma, 2015)
The purpose of this study was to analyze comparative financial performance on a national private banks before and after implementation of the Indonesian Banking Architecture and to analyze the development of the application of the Indonesian Banking Architecture in private banks. This study uses secondary data from quarterly financial statements national commercial banks obtained from the bank during the period of 2002-2006. Sampling technique using purposive sampling method and data analysis methods used are financial ratios CAR, NPLs, ROA, ROE, NIM, ROA and LDR, statistical analysis normality test and two different test paired sample t test. Data processing for both the analyst using SPSS. The results showed that the comparison of the performance of the national private commercial banks before and after implementation of the Indonesian Banking Architecture 2002-2006 period there were no significant differences. Keyword: financial performance, architecture, banking